THE AWARENESS OF GENERATION Z ABOUT MANIFESTATION OF WOMEN’S SUBORDINATION AND MARGINALIZATION - Endah Siswati; Novita Sari; Fera Tara Batari (LENTERA: JOURNAL OF GENDER AND CHILDREN STUDIES, 2025)
Patriarchal ideology breeds subordination and marginalization of women. Gender awareness is key to eliminating both. This descriptive quantitative study examines Generation Z’s gender awareness of the manifestations of subordination and marginalization. The study involved 200 respondents. Data were collected through questionnaires. The study found that generation Z lacks understanding of the manifestations of subordination. This is evident in the majority of respondents who agree that men should be leaders and women should be led. Men should represent the family. Wives are prohibited from working, and all wives activities outside the home must have their husbands permission. Wives must obey their husbands. Generation Z’s awareness of the manifestations of marginalization is better. The majority of respondents disagree that family allowances are only for male workers and that their wages are higher than those of female workers in equivalent jobs. Only a small proportion of respondents agree that men are more suitable as leaders and decision-makers. Only a few respondents agree that women should work at home. The majority of respondents disagree that women are only suitable for unskilled and service-oriented jobs. Socialization to build generation Z’s gender awareness needs to be encouraged for gender justice. Keywords: Gender; Generation Z; Marginalization; Subordination; Women.